1996
DOI: 10.2118/26328-pa
|View full text |Cite
|
Sign up to set email alerts
|

Hole-Cleaning Capabilities of Water- and Oil-Based Drilling Fluids: A Comparative Experimental Study

Abstract: Summary Many laboratory studies evaluating the cuttings transport capabilities of water-based and oil-based drilling fluids have been published. Few attempts have been made to investigate both fluid types under identical, controlled conditions. Those that considered both fluid types measured cuttings accumulation in the annulus and not fluid velocity. In this comparative study, the efficiency of water-based and oil-based muds in cleaning the inclined annulus at varying fluid velocities was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Hareland et al (1993) reported that except at hole inclinations of 40 o to 50 o , oilbased muds and water-based muds with similar rheological properties behave similarly, whereas at 40 o to 50 o hole inclinations water-based muds outperform oil-based muds. Hemphill and Larsen (1996) found out that oil-based and water-based drilling fluids with similar rheological properties and at a particular velocity behave similarly at all the hole inclinations from 0 o to 90 o . Seeberger et al (1989) reported that above a particular fluid velocity, drilling fluids with similar rheological properties behaves in an equivalent fashion, whereas, below that particular fluid velocity water-based mud has better performance that oil-based mud.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hareland et al (1993) reported that except at hole inclinations of 40 o to 50 o , oilbased muds and water-based muds with similar rheological properties behave similarly, whereas at 40 o to 50 o hole inclinations water-based muds outperform oil-based muds. Hemphill and Larsen (1996) found out that oil-based and water-based drilling fluids with similar rheological properties and at a particular velocity behave similarly at all the hole inclinations from 0 o to 90 o . Seeberger et al (1989) reported that above a particular fluid velocity, drilling fluids with similar rheological properties behaves in an equivalent fashion, whereas, below that particular fluid velocity water-based mud has better performance that oil-based mud.…”
Section: Introductionmentioning
confidence: 89%
“…Hemphill and Larsen (1996) provide an overview of laboratory experiments conducted at the University of Tulsa, more than two decades ago. Apparently, not much research has been conducted in this area since then.…”
Section: Introductionmentioning
confidence: 99%
“…al. Некоторые исследования (Zarrough 1991, Brown et al 1989, Ford et al 1990, Peden et al 1990, Larsen 1990, Jalukar 1993, Hemphill et al 1996, Mirhaj et al 2007, Duan et al 2009, Ranjbar 2010, Ozbayoglu et al 2010a, 2010b, Agwu 2012, Bizhani 2013, Corredor 2013 были направлены на определение критической скорости осаждения (КСО), свыше которой не образуется неподвижных слоев. Некоторые исследования (Zarrough 1991, Brown et al 1989, Ford et al 1990, Peden et al 1990, Larsen 1990, Jalukar 1993, Hemphill et al 1996, Mirhaj et al 2007, Duan et al 2009, Ranjbar 2010, Ozbayoglu et al 2010a, 2010b, Agwu 2012, Bizhani 2013, Corredor 2013 были направлены на определение критической скорости осаждения (КСО), свыше которой не образуется неподвижных слоев.…”
Section: краткая история исследований транспорта твердых частицunclassified
“…However, these characteristics are detrimental to well completion and workover operations because they lead to difficult filter-cake cleanup, poor cementing, and the retention of oil on cuttings (Davison et al, 2000;Hemphill and Larsen, 1996;Malachosky et al, 1993;Oakley et al, 1991;Saasen et al, 2001;Yan, 2013). Fluids that are highly oil-wetting also tend to alter the wettability of the drilled formation, resulting in formation damage (Ballard and Dawe, 1998;Chen et al, 2006;Cuiec, 1989;Fjelde, 2009;Gant and Anderson, 1988;McDonald and Buller, 1992;Skalli et al, 2006;Yan et al, 1993;Yan and Sharma, 1989).…”
Section: Introductionmentioning
confidence: 99%